FUNGSI PELAKSANAAN KONTROL SOSIAL TERHADAP RUMAH KOS-KOSAN DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Indra Gunawan; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Simpang Baru Village, Tampan Sub-district, Pekanbaru with the title Social Control Function on Boarding House. This research was intended to know how boarding house rules, what was done by the people or the owner in implementing boarding house regulation, and to know the social punishment that given by society to violator. This research is descriptive qualitative research. The subject in this study was needed 25 people consist of the community, public figure, boarding houses, local youth, the house boardingers and the RT / RW that can help the researcher in the issues that discuss. The determination technique of the subject in this research was used purposive sampling that adjusted to research’s purpose. The researcher collected the data by using guidelines. The results show that there are social control effort by the social control agents to avoid undesirable events in a boarding house environment which can disrupt the security, peace and tranquility of citizens. Kinds of control are performed from night patrols, deliberations, raids, written regulations and sanctions. In the implementation control of the house boardingers in the Simpang Baru villages run ineffective because of the bustle of society around the boarding house so they don’t really care with the boarding house around them. Lack of supervision by the owner of the boarding house around Simpang Baru Village caused wind deviation behavior of the boardingers. But the deviation made by the boardingers still classified in a light deviation and the limits of reasonableness. And also there is no parental control.Keywords : Social Control, Boarding House, Deviant behavior